2021
DOI: 10.1111/acer.14546
|View full text |Cite
|
Sign up to set email alerts
|

Increased Synaptic Strength and mGlu2/3 Receptor Plasticity on Mouse Prefrontal Cortex Intratelencephalic Pyramidal Cells Following Intermittent Access to Ethanol

Abstract: Background The medial prefrontal cortex (PFC) is crucial for regulating craving and alcohol seeking in alcohol use disorder (AUD) patients and alcohol seeking in animal models. Maladaptive changes in volitional ethanol (EtOH) intake have been associated with PFC function, yet synaptic adaptations within PFC have not been consistently detected in voluntary drinking rodent models. At least 80% of the neurons in PFC are glutamatergic pyramidal cells. Pyramidal cells provide the predominant cortical output to seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…For example, metabotropic glutamate (mGlu) receptors offer an interesting target to further clarify the mechanisms of action of psychedelics. Changes in mGlu receptor system have been implicated in intermittent ethanol intake in mice, including increased mGlu 2/3 receptor-mediated long-term depression in the subset of pyramidal cells of the medial prefrontal cortex (Joffe et al, 2021), increased mGlu 5 receptor expression in the nucleus accumbens (Cozzoli et al, 2012), and, furthermore, mGlu2/3 agonist reduces alcohol seeking in mice (Windisch and Czachowski, 2018). Beyond the previously suggested interplay between the mGlu 2/3 receptors and 5-HT 2A receptor (González-Maeso et al, 2008; Toneatti et al, 2020), it was recently shown that psilocybin can recover the alcohol dependence-induced downregulation of mGlu 2 expression in the infralimbic cortex in rats, and that this recovery was correlated with significant reductions in craving-like alcohol-seeking behaviours (Meinhardt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, metabotropic glutamate (mGlu) receptors offer an interesting target to further clarify the mechanisms of action of psychedelics. Changes in mGlu receptor system have been implicated in intermittent ethanol intake in mice, including increased mGlu 2/3 receptor-mediated long-term depression in the subset of pyramidal cells of the medial prefrontal cortex (Joffe et al, 2021), increased mGlu 5 receptor expression in the nucleus accumbens (Cozzoli et al, 2012), and, furthermore, mGlu2/3 agonist reduces alcohol seeking in mice (Windisch and Czachowski, 2018). Beyond the previously suggested interplay between the mGlu 2/3 receptors and 5-HT 2A receptor (González-Maeso et al, 2008; Toneatti et al, 2020), it was recently shown that psilocybin can recover the alcohol dependence-induced downregulation of mGlu 2 expression in the infralimbic cortex in rats, and that this recovery was correlated with significant reductions in craving-like alcohol-seeking behaviours (Meinhardt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found that after protracted abstinence, reduced craving was correlated with improved RSFC between the bilateral SFG and the left OFC (Figure 6). Our results highlight the possible roles of SFG-OFC circuits in craving Joffe, Winder, and Conn (2021). The OFC is a crucial region for controlling goal-oriented behavior in SUD and is thought to be related to the incubation of heroin craving (Altshuler et al, 2021) induced by salient stimuli, which then leads to drug-seeking and drug-taking behaviors.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, an important consideration for future experiments is that neocortical pyramidal cells can be differentiated into several subclasses based on projection target as well as the expression of GPCRs and other proteins. Thus, it is likely that disease-related experiences differentially alter the IN regulation of pyramidal cell subpopulations, as we have observed with respect to excitatory transmission (Joffe et al, 2021). Future studies will need to use a priori means to distinguish cell types to parse subtle or bidirectional changes to specific subpopulations.…”
Section: Figurementioning
confidence: 89%